50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-1094
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy and RANS Simulations of a Normal Shock Train in a Constant-Area Isolator

Abstract: Large-eddy simulations (LES) of a normal shock train in a constant-area isolator (M ∞ = 1.61, Re θ = 1660) are carried out with a high-order compact differencing scheme using localized artificial diffusivity (LAD) for shock capturing. We examine sensitivities of the solution to a variety of physical modeling assumptions. Simulations with spanwise periodic boundary conditions are first performed, the results of which are compared to experiment and validated with a three-level grid refinement study. Due to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Extrapolation was performed at the outlet of the domain where the flow is supersonic, otherwise, a specified pressure value was imposed. Based on [9], the grid employed here was made of 1199, 76, and 98 points in the x-,y-,and z-direction and consisted of 8.93×10 6 points. Hyperbolic stretching is used away from the wall.…”
Section: A Shock Train Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapolation was performed at the outlet of the domain where the flow is supersonic, otherwise, a specified pressure value was imposed. Based on [9], the grid employed here was made of 1199, 76, and 98 points in the x-,y-,and z-direction and consisted of 8.93×10 6 points. Hyperbolic stretching is used away from the wall.…”
Section: A Shock Train Simulationsmentioning
confidence: 99%
“…Numerical work by Giglmaier et al [5] is one of the few that show in detail the benefits of using RSM-based turbulence models for shock train simulations. Scale resolving methods such as LES [6,7] and WMLES [8] show promising results, however, the Reynolds number must often be reduced for the former, and the latter relies on near-wall modelling which may not be applicable in separated regions. Previous investigations performed by Boychev et al [9] showed that the use of the k-ω EARSM turbulence model improves the shock train predictions of the experiment by Carroll et al [10] by reducing pressure oscillations occuring at the wall.…”
Section: Introductionmentioning
confidence: 99%
“…VER the past few decades, a considerable number of studied have been conducted on supersonic combustion ramjet (scramjet) engines expected to be suitable for use as next-generation propulsion systems [1][2][3] . Dual-mode scramjet engines provide a practical solution to supersonic flight by operating under a wide range of Mach numbers.…”
Section: Introductionmentioning
confidence: 99%
“…17 Side-wall effects have also proven important in computational models. Morgan et al 18,19 demonstrated the effects of inclusion or noninclusion of side-walls on the boundary layer growth and found that fully resolving the side-walls may result in unstart. While computational models are getting better at predicting shock train structure, there are still many aspects of shock trains that cannot be predicted with simulations.…”
Section: Introductionmentioning
confidence: 99%